USER EXPERIENCE ANALYSIS OF WEB GEOGRAPHIC INFORMATION SYSTEM (WEBGIS) OF SENIOR AND VOCATIONAL HIGH SCHOOL EDUCATION FACILITIES IN KLATEN REGENCY, INDONESIA (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2023)
Government policies that stipulate 12 years of compulsory education require an area to have adequate advanced education facilities such as senior high school (SMA) and vocational high school (SMK). The distribution of SMA/SMK in Klaten is still uneven and some sub-districts still lack SMA/SMK. The lack of spatial information related to the distribution of SMA/SMK makes it difficult to evenly distribute the provision of SMA/SMK. The objectives of this study are 1) to visualize the distribution of SMA/SMK using a Web Geographic Information System (WebGIS) based on Story Maps and 2) to evaluate the user experience of Story Maps of the distribution of SMA/SMK in Klaten Regency. The location points of SMA/SMK in Klaten were obtained from Google Maps and field surveys. The SMA/SMK were mapped using Story Maps. User experience evaluation was done by using online questionnaires. The results of the Story Map of the distribution of public and private SMA/SMK in Klaten Regency showed that the distribution pattern of public vocational school institutions tended to be clustered in the central part of Klaten area. The results of the user experience test (range of scores 1-5) showed that the learnability aspect was 4.57, the efficiency aspect was 4.40, the memorability aspect was 4.10, the errors aspect was 2.19, the satisfaction aspect is 4.12. Overall, users rate the average of all aspects of 3.88, in other words, the Story Maps made are quite good and acceptable by the users.